Del propósito de la filosofía (2010)
It is vital to ask what to teach in philosophy and how; but to address this question; we must first determine with what purpose to do it; but above all; to know what isthe purpose of philosophy. Perhaps by determining the essential basis it would be clearer to answer the question of teaching and learning; even more; all this will help to clarify the mission of the philosophy and the philosopher today. To resolve this ponder is a philosophical reflection on traditional academic practices. Then; from some authors; it is made a dissertation on what is philosophy; to deduce in which aspects of the current academic practices is present or distant the philosophy. Finally we propose some perspectives to extend the philosophy and teaching of philosophy.